2021
DOI: 10.1016/j.ebr.2021.100442
|View full text |Cite
|
Sign up to set email alerts
|

Improving public stigma, sociocultural beliefs, and social identity for people with epilepsy in the Aseer region of Saudi Arabia

Abstract: Highlights An update of the data reported previously in 2016 in Aseer region. The level of education and awareness regarding epilepsy in Aseer region has improved recently. The belief in spiritual and traditional therapies has decreased, considering them as additional options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…It was found that the HRQOL of children with epilepsy should be considered beyond the microsystem directly related to the child. Community resources, such as healthcare facilities for disease management, psychosocial interventions, epilepsy-related education, school personnel trained to deal with and handle seizure attacks, and facilities free of physical damage, have been used as external systems to improve HRQOL in children with epilepsy [ 5 , 32 , 35 , 41 , 43 - 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the HRQOL of children with epilepsy should be considered beyond the microsystem directly related to the child. Community resources, such as healthcare facilities for disease management, psychosocial interventions, epilepsy-related education, school personnel trained to deal with and handle seizure attacks, and facilities free of physical damage, have been used as external systems to improve HRQOL in children with epilepsy [ 5 , 32 , 35 , 41 , 43 - 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 40.1% are convinced that it is due to a spiritual reason. 6 Likewise, according to a study conducted among the Kuwaiti population, 88.3% indicated that putting an object in the patient's mouth to prevent him from biting his tongue during a seizure is appropriate. 20 Furthermore, according to the results of a survey conducted among a sample of people with a high level of education in Tehran, 17% indicated that the will of God was the cause.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Epilepsy is often related to the misconception, fear, stigma, and myths in the general population and even among healthcare professionals. [5][6][7][8] In many parts of the world, and primarily in low-and middle-income countries, more than 75% of people with active epilepsy are untreated, which is a health and economic burden. 9 Indeed, several psychosocial and cultural factors are important determinants of the clinical course of epilepsy and are often among the main barriers to appropriate care and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that 374 (94.9%) of the students agreed that epilepsy is not contagious, and 215 (54.6%) of the students denied the impact of epilepsy on patients’ marital status, relationships, and fertility. In a survey done by Ghaffar et al 18 in the Aseer region of Saudi Arabia, 95.8% of the participants disputed that epilepsy is a contagious illness. The population’s knowledge regarding epilepsy improved in KSA in the past few years as the percentage of believers in epilepsy as contagious decreased in different regions decreased relatively.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is in line with the findings of other studies. 18 , 21 , 22 Approximately 334 (84.8%) respondents believe epilepsy is a disease, while 123 (31.2%) believe epilepsy is a supernatural phenomenon or black magic, indicating a negative attitude toward epilepsy, implying that despite public awareness efforts and modern education, a negative perception of PWE still exists in Saudi Arabia. This situation also exists in other Middle Eastern nations, such as the United Arab Emirates 25 and Iran.…”
Section: Discussionmentioning
confidence: 99%